La investigación filosófica desde la relación: una mirada panorámica a la luz de una propuesta metodológica - Cisneros Arellano, José Luis (2021)
The purpose of this paper is to indicate that the ontological notion of relation as relation has been key for the development of the most representative philosophical methods. In this regard, at the end of the article, I propose a particular methodological perspective for philosophical research. To get there, I begin with a brief historical review of some basic epistemological and ontological aspects of each method. Secondly, I present my proposal and suggest that philosophical research can be supported by empirical or documentary evidence that, in interface with axioms and ontological postulates, undergo a validation process established on two theorems: essence and possibility. I have called this philosophical engineering process.